Program-target approach in support of tourism development: Experience of foreign countries - N. S. Sergienko (Вестник университета)
The article studies program measures to support tourism industry development abroad. Experience of individual countries allows us to highlight systemic measures aimed at developing tourism infrastructure facilities and creating new jobs both in the industry itself and in related areas. The set of adopted documents in response to the consequences of the COVID-19 pandemic is aimed at multifaceted assistance to the tourism business and support of its employment. The results of generalizing the complex of program-targeted documents on the financial provision of implementing tourism support programs have been presented on the example of the experience of individual countries. The article shows that individual programs supporting the tourism industry in foreign countries with a social orientation are relevant, which allows to obtain a synergetic effect from forming a strategic approach in developing measures to support tourism through targeted programs.